Antibody- Based Immunotherapy Combined With Antimycotic Drug TMP- SMX to Treat Infection With Paracoccidioides brasiliensis - Boniche-Alfaro, Camila; Kischkel, Brenda; Thomaz, Luciana; Carvalho-Gomes, Monique Maria; Lopes-Bezerra, Leila M.; Nosanchuk, Joshua Daniel; Taborda, Carlos Pelleschi (Frontiers in Immunology, 2021)
Monoclonal antibodies (mAbs) are promising alternatives to treat infectious diseases, especially given their potential for applications in combination therapies with antimicrobial drugs to enhance the antifungal efficacy. Protection mediated by mAbs used to treat experimental paracoccidioidomycosis (PCM) has been demonstrated previously. Our aim in the present work was to characterize a monoclonal antibody (mAbF1.4) raised against a cell wall glycoconjugate fraction of Paracoccidioides spp. and to analyze its efficacy combined with trimethoprim-sulfamethoxazole (TMP/SMX) as treatment for experimental PCM. We demonstrated that the epitope recognized by mAbF1.4 is consistent with branched glucose residues present on a cell wall β-glucan polymer. In vitro, mAbF1.4 increased the phagocytic capacity and nitric oxide concentration induced by the macrophage cell line J774.1A, and this resulted in a significant reduction in the viability of the opsonophagocytized yeasts. In vivo, we detected a significant reduction in pulmonary fungal burdens of mice treated with mAbF1.4 in association with TMP/SMX, which correlated with increased pulmonary concentrations (determined by ELISA) of IFN- γ, TNF-α, IL-10 and IL-17. In parallel, we observed a decrease in IL-4, suggesting that the treatment was associated with a mixed Th1-Th17 type immune response. Histopathology of lung segments from mice receiving the combination therapy showed a significant reduction in granulomas, which were well-defined, and improved maintenance of lung architecture. These findings demonstrate that mAbF1.4 + TMP/SMX therapy is a promising approach to combat PCM as well as decrease disease sequelae and highlights the potential benefits of immune mediators in PCM combined immunotherapy.